Arte e Sagrado: relações de imanência e sua presença na prosa contemporânea de Hilda Hilst - Silva, Leandro Soares da (2008)
This thesis has two goals: first, it discusses how the Holy remains in Art and proposes a view to studying the events of the sacred in prose; the second goal is to demonstrate, from the analysis of three narratives by Hilda Hilst, as her texts share a mystical and philosophical tradition about the sacred and how they have characteristics that indicate the immanence of the holy in her work. It also sought to define the way the author thinks an idea of God and Godhead that occupies a place in her work. Thus, this study shows the permanence of the holy in arts, and a way to study it in contemporary prose from a comparative perspective based in texts from other areas of knowledge, as the anthropological and philosophical studies.